Mencapai Keselamatan dengan Perlindungan Dewa dan Rajah: Kajian Ilustrasi Lontar Merapi Merbabu (9 L 197) - Dwiadmojo, Ghis Nggar (Perpustakaan Nasional RI, 2023)
Research on aspects of the manuscript, including the illustrations, has been carried out by many researchers. This is important because it is considered to be able to reveal the contents of a text more thoroughly. The manuscript with code 9 L 197, collection of the National Library of Indonesia, is one of the lontar manuscripts originating from the Merapi Merbabu scriptoria which has many illustrations. The purpose of this research is to describe and reveal the meaning of illustrations in manuscript 9 L 197 based on reading the supporting text. The approach used is the philological and image semiological approach of Roland Barthes. The results of the study show that the text in manuscript 9 L 197 was copied using the Buda script and Javanese language. The text in this manuscript are Pagrahanan, Palilindon, and Respatikalpa. This manuscript contains 89 illustrations. Based on their shape, these 89 illustrations can be classified into four groups, namely illustrations in the form of human (I), illustrations in the form of animal (II), illustrations in the form of mythological creature (III), and illustrations in the form of inanimate object (IV). Based on the reading of the supporting texts, except for subgroup Ic, it can be concluded that the purpose of illustrations in this manuscript aims to achieve salvation. The salvation includes being loved, survived from wild animals, survived from fights, survived from crop failure due to pests, survived from disease, survived from unsold trade, survived from love spells, survived by worshiping Brahma and Vishnu, salvation on food and housing, salvation related with kecubung plant (Datura metel) and betel leaf (Piper betle linn).